Designing Listening Tasks For English Students - Irwan D, Darwissyah; Indrasari, Nunun (Universitas Islam Negeri Raden Intan Lampung, 2019)
Listening skill is one of important skills in learning English. Therefore, it is considered as difficult skill for the students. Designing tasks for listening skill is also challenging for the teachers. This paper describes possible ways in designing listening tasks for the students. The descriptions include definition, the types of tasks, and the possible ways of designing task for listening skills based on the types of listening performance